If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = -27y + 7 + -1(-15y) + 13 Remove parenthesis around (-15y) -4 = -27y + 7 + -1 * -15y + 13 Multiply -1 * -15 -4 = -27y + 7 + 15y + 13 Reorder the terms: -4 = 7 + 13 + -27y + 15y Combine like terms: 7 + 13 = 20 -4 = 20 + -27y + 15y Combine like terms: -27y + 15y = -12y -4 = 20 + -12y Solving -4 = 20 + -12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12y' to each side of the equation. -4 + 12y = 20 + -12y + 12y Combine like terms: -12y + 12y = 0 -4 + 12y = 20 + 0 -4 + 12y = 20 Add '4' to each side of the equation. -4 + 4 + 12y = 20 + 4 Combine like terms: -4 + 4 = 0 0 + 12y = 20 + 4 12y = 20 + 4 Combine like terms: 20 + 4 = 24 12y = 24 Divide each side by '12'. y = 2 Simplifying y = 2
| -4=-2+x | | 83y+5=10 | | 2(1-3x)=2(-4x+7) | | 4[2.5+3(20+7)]= | | 7(x+1)=(-1)(7x+7) | | 2(z+1)-2x=2 | | 8x-4-2x-11=27 | | 13=(-4x)+9 | | 3x-7-10=-8 | | x^6y^9+216z^3=0 | | 3(m+6)+7(m-2)= | | 5(x-1)=8(x+1) | | ln(2-6x)=-1 | | 5.1/2+p=6 | | 9(2x-5)=3 | | X^2+3x^3-4x=0 | | 4(a+2)=14-2(2x-1) | | x+2=(5+2x) | | -12x--28=340 | | 3t+2t+4t=-63 | | 2(x-4)-12=2(4x-1) | | 2t+8r+6p=64 | | x+4/2-3=19 | | V=YLJfory | | -2x+-2=2 | | 1.35=0.3v | | 2160=(27000)(0.04)T | | x=12t^3-18t^2+2t+5 | | 4y+3+53=180 | | AC+2B= | | 3y=-12x+9 | | (13-3)+5-6= |